A TEENAGERS’ COMMUNICATION COMPETENCIES IN USING SOCIAL MEDIA - Fricilia Bernadetha; Chontina Siahaan (Sociae Polites, 2021)
In the digitalization era nowadays, the use of social media has a huge impact on the lives of children and teenagers. Social media produces both positive and negative impacts. The positive impact of social media is to help and support their daily lives such as making it easier for the children and the teenagers to complete their school assignments. In the other side, some of the negative impacts of using social media that hinders human life such as isolating an individual from his group and accessing inappropriate information for children which can endanger their lives. One of the good impacts of social media on children and teenagers is that they can learn how to communicate well and connect with other people through social media. They can also learn foreign languages by connecting to foreigners through social media. There are more good impacts on them by using social media. However, there are also bad impacts on the children in using social, one of which is the possibility for them being connected to any individuals or any communities that can negatively impact on them and even endanger their lives. Keywords: Teenager, social media, communication